2010
DOI: 10.1007/s00468-010-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of wood formation in Oriental beech (Fagus orientalis Lipsky) along an altitudinal gradient in the Hyrcanian forest, Iran

Abstract: The cambium dynamics and wood formation of Oriental beech (Fagus orientalis Lipsky) was investigated during the 2008 growing season in the Nowshahr Hyrcanian forest, Iran (36°N, 51°E). Three study sites were selected along an altitudinal gradient (650, 1,100 and 1,600 m a.s.l.), and cambial activity rates of cell formation and cell maturation were studied on micro-cores collected in intervals of 10-20 days. The cambium reactivation of the low-altitude (L) and mid-altitude (M) trees occurred contemporaneously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 41 publications
9
26
0
Order By: Relevance
“…For the populations in Bacau -especially from the one located at the lower altitudinal limit -the negative correlation with summer temperature and the positive correlations with summer precipitations point to the fact that the summer (i.e. June) water availability is the main driving factor of growth for beech trees, in accordance with the results from other studies (Bouriaud et al, 2004;Michelot et al, 2012;Oladi et al, 2011). In addition, the results suggest that the water availability during September (the previous year) was an important factor for the growth formation, probably due the contribution of the soil water reserve.…”
Section: Seedlings Analysissupporting
confidence: 88%
“…For the populations in Bacau -especially from the one located at the lower altitudinal limit -the negative correlation with summer temperature and the positive correlations with summer precipitations point to the fact that the summer (i.e. June) water availability is the main driving factor of growth for beech trees, in accordance with the results from other studies (Bouriaud et al, 2004;Michelot et al, 2012;Oladi et al, 2011). In addition, the results suggest that the water availability during September (the previous year) was an important factor for the growth formation, probably due the contribution of the soil water reserve.…”
Section: Seedlings Analysissupporting
confidence: 88%
“…In their studies, Cufar et al (2008a) found that about 76% of the annual ring was formed by the end of June, whilst, in similar studies in Czech Republic, the percentage reached 65% (Vavrcik et al, 2013). The results showed that June had the highest importance in the radial growth, an observation that has also been confirmed by other studies (Bouriaud et al, 2004;Michelot et al, 2012;Oladi et al, 2011). However, the maturation of cells (complete lignification process) continues even after the cessation of the cambial division (Gricar et al, 2005;De Luis et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Most dendroclimatological studies are based on the analysis of the statistical relationship between the width of tree rings and the climatic factors from current and previous growing seasons (Schweingruber, 1992). Only few studies addressed the problem of intra-annual variation of the treering characteristics, respectively the dynamics of beech radial growth phases (Schmitt et al, 2000;Bouriaud et al, 2004;Oladi et al, 2011;Prislan et al, 2013;Vavrcik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2). In natural stands, the onset of cambial activity occurs within a relatively narrow range of daily minimum air temperature (+2 to +7°C in 80% of the data; Rossi et al 2008), resulting in altitudinal gradients of cambium resumption (Moser et al 2010;Oladi et al 2010;Prislan et al 2013). Moreover, the resumption of cambial activity can be triggered during late winter by an artificial heating of tree stems (Oribe et al 2003;Begum et al 2007Begum et al , 2010.…”
Section: The Phenology Of Wood Formationmentioning
confidence: 99%
“…Indeed, the cessation of the division of cambial initials in late summer or autumn occurs at considerably milder temperatures than those for spring resumption (between +5°C and +13°C for gymnosperms, Rossi et al 2008), but cessation can be hastened by artificial cooling (Gričar et al 2007). This equivocal role of temperature results in the absence of clear altitudinal gradients in the timing of the cessation of cambial activity (Moser et al 2010;Oladi et al 2010;Prislan et al 2013). This body of results clearly demonstrates that cambium division does not simply respond to the occurrence of certain temperature thresholds but that other environmental cues are involved in the timing of cambium activity.…”
Section: The Phenology Of Wood Formationmentioning
confidence: 99%